Free throw deep dives: Picking your spot - Beuoy. M. (Inpredictable, 2017)
The purpose of these posts is to assess what makes for good free throw shooting. The NBA's SportVU system tracks the position of the ball in all three dimensions. I have taken that raw, often messy data and organized it using some freshman level physics. From that simple model, I have created a whole host of new descriptive statistics on player shooting mechanics.